A Preliminary Examination of Acceptance and Commitment Therapy Versus Exposure and Response Prevention for Patients with Obsessive-Compulsive Disorder on an Optimal Dose of SSRIs: A Randomized Controlled Trial in Iran. Issue 3 (May 2022) - Zemestani, Mehdi; Salavati, Mojgan; Seyedolshohadayi, Asrin; Petersen, Julie M.; Ong, Clarissa W.; Twohig, Michael P.; Ghaderi, Ebrahim
This study compared the effects of adding acceptance and commitment therapy (ACT) or exposure and response prevention (ERP) to adults diagnosed with obsessive compulsive disorder (OCD) already on an optimal and stable dose of selective serotonin reuptake inhibitors (SSRIs). Forty adults on SSRIs who were diagnosed with OCD participated in a randomized controlled trial in Iran of 12 individual weekly sessions of either ACT+SSRI, ERP+SSRI, or continued SSRI only. The results showed significant reductions in OCD symptom severity in ACT+SSRI and ERP+SSRI conditions at posttreatment with significantly greater reductions in both conditions compared to SSRI-only at follow-up. Additionally, psychological inflexibility and use of thought control strategies significantly decreased in the ACT+SSRI condition at posttreatment and follow-up compared to the ERP+SSRI and SSRI conditions. Both conditions led to decreases in perceived importance of stop signals. Results provide cross-cultural support for the treatment of OCD using ACT and ERP as adjuncts to SSRI and modest process of change differences between ACT and ERP. Future directions and study limitations are discussed.